PENERAPAN GREEN MANAGEMENT SEBAGAI STRATEGI PERUSAHAAN DALAM MENGHADAPI KONDISI LINGKUNGAN - Sabita Julianda, Putri; Simanjorang, Feronica (Journal Business Administration: Entrepreneurship and Creative Industry, 2022)
The most significant environmental damage can occur due to the large number of industrial activities. The development of technology and industry has greatly increased the use of natural resources and energy sources. The waste generated is known to have an impact on environmental damage. Corporate responsibility (CSR) in managing the environment can help restore environmental conditions. By using literature study, the author aims to describe the form of green management implementation by The Body Shop by looking at the application of marketing mix that has been done. The author collects secondary data sourced from websites, journals, and news. The researcher found that The Body Shop, both externally and internally, has carried out various activities in line with the concept of green management such as 3R and various campaigns to protect the earth.